Situation Report: Poland, 28 December 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Conference on the Middle East New Warsaw City Party Secretary Kliszko on Industrial Cadres Cyrankiewicz's Activities Cardinal Wyszynski on Need for New Churches Speeches of Catholic Sejm Deputies Moczar's Visit to Moscow Polish-Austrian Cultural Agreement Polish-Albanian Trade Protocol